HDAC inhibition for optimized cellular immunotherapy of NY-ESO-1-positive soft tissue sarcoma - Gong, Wenjie; Wang, Lei; Schubert, Maria-Luisa; Kleist, Christian; Neuber, Brigitte; Wang, Sanmei; Yang, Mingya; Hückelhoven-Krauss, Angela; Wu, Depei; Schmitt, Anita; Müller-Tidow, Carsten; Shiku, Hiroshi; et al. (Biomedicines, 2022)
Adoptive cell therapy with NY-ESO-1-specific T cells is a promising option for the treatment of soft tissue sarcoma (STS) but achieves only transient tumor control in the majority of cases. A strategy to optimize this cell therapeutic approach might be the modulation of the expression of the cancer-testis antigen NY-ESO-1 using histone deacetylase inhibitors (HDACis). In this study, the ex vivo effect of combining NY-ESO-1-specific T cells with the clinically approved pan HDACis panobinostat or vorionstat was investigated. Our data demonstrated that STS cells were sensitive to HDACis. Administration of HDACi prior to NY-ESO-1-specific T cells exerted enhanced lysis against the NY-ESO-1+ STS cell line SW982. This correlated with an increase in the NY-ESO-1 and HLA-ABC expression of SW982 cells, as well as increased CD25 expression on NY-ESO-1-specific T cells. Furthermore, the immune reactivity of NY-ESO-1-specific CD8+ T cells in terms of cytokine release was enhanced by HDACis. In summary, pretreatment with HDACis represents a potential means of enhancing the cytotoxic efficacy of NY-ESO-1-specific T cells against NY-ESO-1-positive STS.